Students' Conceptions on the Topic of Desertification: Results of a Qualitative Interview Study with 12- and 13-Year-Old Students - Schubert, Jan Christoph (Journal of Geography Education, 2013)
Preconceptions are a crucial factor in the educational learning process. Therefore, the investigation of preconceptions is important for learning and teaching also in the field of geography. This study examines the preconceptions of 12- and 13-year-old students on the major environmental problem of desertification. The students' preconceptions were collected by conducting problem-centered interviews. These interviews (n=13) were then evaluated using qualitative content analysis. Results show quite complex preconceptions concerning causes, processes, effects and measures to counter desertification. Regarding the causes of desertification, three basic preconceptions were identified: water consumption inducing drought, climate change generating high temperatures and wind blowing sand from deserts to adjacent areas. All in all, natural causes for desertification are dominant in the students' perspective. In conclusion, some conceptions can be classified as alternative ones, whilst others are almost in line with scientific explanations. Based on the results of the study, implications concerning learning and teaching geography are proposed, such as focusing on the anthropogenic causes of desertification.
Keywords: preconceptions, alternative conceptions, desertification, interview study, qualitative content analysis